Temperature, productivity, and income - Olivier Deschênes (IZA World of Labor, 2023)
Climate change is rapidly deteriorating environmental conditions through droughts and floods, hurricanes, wildfires, rising temperatures, and more frequent and longer heatwaves. A growing literature has shown how higher temperatures reduce worker productivity and economic output. These effects are more pronounced in poorer countries and in climate-exposed economic sectors like agriculture, construction, and manufacturing. The development of new technologies that mitigate exposure to heat among workers, combined with better temperature control in the workplace, will be essential to reduce the economic burden of climate change.
Keywords: F64; O44; P18; Q5; 330; extreme temperature; climate change; productivity; gross domestic product